Seismic performance evaluation of multi-storied RC structures by nonlinear static analysis - Md. Foisal Haque; Md. Mahmodul Hasan Rahat; Md. Mozammel Hoque (Results in Engineering)
There is no proper specification about response reduction factor for various configured structures in the latest version of Bangladesh National Building Code (BNBC 2020). This research proposes various configured multi-storied reinforced concrete (RC) structures for the evaluation of roof displacement, ductility, strength ratio, and response reduction factor under seismic loading by using nonlinear static analysis. Four configured RC structures are used in this research such as flat plate with edge beam, flat plate without edge beam, flat plate with drop panel, and beam-column supported framing system. The multi-storied are considered to be 6, 9, 12, and 15 with bay widths of 5, 6, and 7 m. The range of difference in validation result is found to be (1.29 to 1.65) %, which may indicate a good accuracy to conduct nonlinear static analysis by using ETABS V 18.1.1. The ductility of flat slab with drop panel is increased at rates of 31.2 % and 37.1 % from the flat plate with edge beam and beam-column supported framing system, respectively. The response reduction factors for the flat plate with edge beam, flat slab with drop panel, and beam-column supported framing systems are found to be 5.4, 5.9, and 6.7, respectively. These values may be added to the BNBC 2020 for the practical application on the RC structures. In addition, the difference in response reduction factors between BNBC 2020 and ASCE 7-05 is found to be 8 %, which may indicate the applicability of BNBC to evaluate seismic performance of RC structures.